Effect of Abiotic Factors on Seasonal Incidence of Whitefly, Bemisia tabaci on Tomato (Solanum lycopersicum L.) Crop - , Ingole D.B.; , Shinde B.D.; , Karmarkar M.S.; , Sanap P.B.; , Kadam J.J. (Archives of Current Research International, 2024)
A field experiment was conducted during the Rabi seasons of 2021-22 and 2022-23 to study the influence of various meteorological parameters on the population dynamics of whitefly, Bemisia tabaci (Hemiptera: Aleyrodidae), infesting tomato (Solanum lycopersicum L.). The study was carried out at the Central Experiment Station, Wakawali, Dr. Balasaheb Sawant Konkan Krishi Vidyapeeth, Dapoli. During Rabi 2022-23, the whitefly population ranged from 0.07 to 7.13 per three leaves per plant, while in Rabi 2023-24, it ranged from 0.05 to 7.52 per three leaves per plant. The peak population of whitefly was consistently observed during the 13th Standard Meteorological Week (SMW) in both seasons. Pooled data for both years revealed that the whitefly population ranged from 0.06 to 7.33 per three leaves per plant, with a peak observed during the 13th SMW. Correlation analysis showed that the whitefly population had a significant negative correlation with evening relative humidity (r = -0.685) but a significant positive correlation with evaporation (r = 0.760**) and wind speed (r = 0.803**). In Rabi 2023-24, the whitefly population was positively correlated with maximum temperature (r = 0.648**), bright sunshine hours (r = 0.618**), wind speed (r = 0.940**), and evaporation (r = 0.875**), while showing a significant negative correlation with morning relative humidity (r = -0.649**).The coefficient of determination (R²) indicated that weather parameters contributed to 90% and 91% of the total variation in the whitefly population during Rabi 2022-23 and 2023-24, respectively. The findings highlight the critical role of meteorological factors in influencing the population dynamics of B. tabaci on tomato during the Rabi season.